2013
DOI: 10.1021/ol4031233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfones from Organozinc Reagents, DABSO, and Alkyl Halides

Abstract: Organozinc reagents react with the SO2 surrogate DABSO, and the resulting zinc sulfinate salts are alkylated in situ to afford sulfones. This transformation has a broad scope and is compatible with a wide range of structural motifs of medicinal chemistry relevance including nitrile, secondary carbamates, and nitrogen-containing heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(44 citation statements)
references
References 38 publications
0
44
0
Order By: Relevance
“…Rocke and co-workers reported that organozinc reagents reacted with DABSO and the resulting zinc sulfinate salts were alkylated in situ to afford sulfones [38]. This transformation has a broad scope and is compatible with a wide range of functional groups including nitrile, secondary carbamates, and nitrogen-containing heterocycles (Fig.…”
Section: Synthesis Of Sulfonesmentioning
confidence: 99%
“…Rocke and co-workers reported that organozinc reagents reacted with DABSO and the resulting zinc sulfinate salts were alkylated in situ to afford sulfones [38]. This transformation has a broad scope and is compatible with a wide range of functional groups including nitrile, secondary carbamates, and nitrogen-containing heterocycles (Fig.…”
Section: Synthesis Of Sulfonesmentioning
confidence: 99%
“…792187) was invented (Figure 1D). PSMS ( 6 ) can be synthesized in one step from bromomethyl phenyl sulfone ( 5 ) 11 and is a free-flowing, bench-stable (stable at room temperature under air over 4 months), white powder whose structure was characterized by X-ray crystallography as the hexahydrate. PSMS ( 6 ) enables the installation of a (phenylsulfonyl)methyl group onto a heteroarene at both an early and late stage of the synthesis.…”
mentioning
confidence: 99%
“…For example, in situ treatment of the sulfinate with an alkyl bromide delivers alkylaryl sulfone products ( 6a–e ). 25 The use of epoxides as the electrophiles provides β-hydroxy sulfones ( 6f–j ). 25 b Treatment with in situ generated chloroamines provides sulfonamides ( 6k–o ), 26 and treatment with NFSI, which is a source of electrophilic fluorine, generates the corresponding sulfonyl fluorides ( 6p–t ).…”
Section: Resultsmentioning
confidence: 99%